Increasing dominance of terrigenous organic matter in circumpolar freshwaters due to permafrost thaw - Wauthy, Maxime; Rautio, Milla; Christoffersen, Kirsten S.; Forsström, Laura; Laurion, Isabelle; Mariash, Heather L.; Peura, Sari; Vincent, Warwick F. (Limnology and oceanography letters, 2018)
Climate change and permafrost thaw are unlocking the vast storage of organic carbon held in northern frozen soils. Here, we evaluated the effects of thawing ice‐rich permafrost on dissolved organic matter (DOM) in freshwaters by optical analysis of 253 ponds across the circumpolar North. For a subset of waters in subarctic Quebec, we also quantified the contribution of terrestrial sources to the DOM pool by stable isotopes. The optical measurements showed a higher proportion of terrestrial carbon and a lower algal contribution to DOM in waters affected by thawing permafrost. DOM composition was largely dominated (mean of 93%) by terrestrial substances at sites influenced by thawing permafrost, while the terrestrial influence was much less in waterbodies located on bedrock (36%) or with tundra soils unaffected by thermokarst processes (42%) in the catchment. Our results demonstrate a strong terrestrial imprint on freshwater ecosystems in degrading ice‐rich permafrost catchments, and the likely shift toward increasing dominance of land‐derived organic carbon in waters with ongoing permafrost thaw.